2014
DOI: 10.1007/s11033-014-3321-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR pathway attenuates migration and invasion of gallbladder cancer via EMT inhibition

Abstract: Gallbladder cancer (GBC) is an aggressive disease in which epithelial-mesenchymal transition (EMT) plays a critical role. Whether inhibition of mTOR effects via EMT reversal in GBC remains unclear. Using genetic and pharmacologic inhibitions of mTOR, we investigated the changes of EMT levels in GBC cells. Expressions of EMT related genes were also studied. Migration and invasion assays were carried out and in vivo tumour metastasis mouse models were established. Circulating tumour DNA was quantified. We used E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 16 publications
3
56
0
Order By: Relevance
“…In order to explore the roles of EMT-related proteins on metastasis when pCREB is diminished, we determined the expression of E-cadherin, which is one of epithelial markers supposed to be down-regulated during EMT. Vimentin, fibronection and N-cadherin, which are mesenchymal markers should be up-regulated during EMT [34]. Our results showed that DNCREB increased the expression of E-cadherin, in contrary, fibronection and N-cadherin was repressed in cells transfected with DNCREB.…”
Section: Pcreb-mediates Rcc Cell Metastasis Is Not Via Vimentinmentioning
confidence: 57%
“…In order to explore the roles of EMT-related proteins on metastasis when pCREB is diminished, we determined the expression of E-cadherin, which is one of epithelial markers supposed to be down-regulated during EMT. Vimentin, fibronection and N-cadherin, which are mesenchymal markers should be up-regulated during EMT [34]. Our results showed that DNCREB increased the expression of E-cadherin, in contrary, fibronection and N-cadherin was repressed in cells transfected with DNCREB.…”
Section: Pcreb-mediates Rcc Cell Metastasis Is Not Via Vimentinmentioning
confidence: 57%
“…For example NAC has been shown to inhibit mammalian target of rapamycin (mTOR; [59]), possibly by decreasing ROS and consequently inhibiting the positive feedback between mTOR and ROS [60]. As mTOR has been implicated in EMT [61, 62], it is a possibility that some of the changes induced by MMP-3-induced ROS could be associated with the mTOR pathway. This possibility is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gulhati et al provided evidence of mTORC1/2 regulating epithelial–mesenchymal transition (EMT), motility, and metastasis in colorectal cancer [9]. Furthermore, Gupta et al and others demonstrated a role for mTORC2 specifically to positively regulate TGFβ signaling in cancer cell migration and invasion [810, 32, 33]. Thus, RICTOR amplification likely promotes increased cell motility in vitro via increased mTORC1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%